Prevalence of Eye Injuries in the Professional Practice of a Dentist and Their Prevention. Part 1 - Skibitskyi, В. С.; Ryzhova, І. П. (Actual Dentistry, 2025)
Relevance. Dentists are at a high-risk zone because various instruments used in tooth preparation generate aerosol clouds and release fine particles, increasing the likelihood of these particles entering their eyes. Additionally, it is important to consider the chemical impact of various disinfectants, filling materials, and reagents, which may also affect the condition of the conjunctiva and cornea. Given the obvious threat to eye health, preventing and protecting dentists’ eyes remains relevant. Aim: our study aimed to analyze the characteristics of anterior eye surface damage in dentists during the preparation of anterior teeth for fixed prosthetic restorations, depending on the type of eye protection used and workplace ergonomics. Materials and Methods. The study was conducted from September 2024 to January 2025 at the Department of Prosthetic Dentistry and the Department of Ophthalmology of the National Medical University, named after O. O. Bogomolets, Kyiv. 54 dentists participated in the study, all performing anterior tooth preparation for fixed prosthetic restorations. Depending on the type of eye protection used, the dentists were divided into three groups (18 dentists): I —regular protective glasses, II — protective glasses with side shields and an adjustable-length magnifying loupe for optimal visibility, and III — dental face shield. We also examined eye damage dependent on ergonomics, specifically the patient’s positioning in the dental chair: 22 patients were treated in a lying position, while 22 were treated in a sitting position. Results. During our study, dentists performing prolonged deep preparation of anterior teeth were found to have sustained traumatic damage from foreign bodies (hard tissue particles, tooth tissue) to the conjunctiva and cornea, as well as eye infections caused by biologically active fluids, aerosols, and soft dental deposits in 11 (13 eyes) out of 54 dentists (20.4%), two dentists suffered bilateral eye damage. The first group has six doctors (33.3%), the second group has 2 (11.1%), and the third group has 3 (16.7%). The occurrence of eye damage in participating dentists was also directly influenced by ergonomics. Conclusions. Dentists should prefer glasses with side protection and adjustable arm length, and follow ergonomic rules when preparing abutment teeth of the anterior group for fixed orthopedic structures.